A circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters and a preparation method thereof

By synthesizing chiral copper nanoclusters using easy-to-get copper raw materials, and interacting with Triton X-100 through hydrogen bonding to construct supramolecular assembly, the complex and cost-effective synthesis of circularly polarized luminescent chiral metal nanoclusters in the prior art is solved, and efficient and economical preparation of circularly polarized luminescent chiral liquid crystals is achieved.

CN116286022BActive Publication Date: 2025-03-25SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310277462.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-25
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively synthesize chiral metal nanoclusters with circularly polarized luminescent properties, and the synthesis process is complex and the cost is high.

Method used

Chiral copper nanoclusters were synthesized using easy-to-access and low-priced copper as raw materials, and interacted with Triton X-100 through hydrogen bonding to construct an ordered molecularly arranged supramolecular assembly through colloid self-assembly to obtain circularly polarized luminescent chiral liquid crystal.

Benefits of technology

A chiral liquid crystal that is prone to circularly polarized luminescence in the excited state is realized, which simplifies the synthesis process, reduces costs, and broadens the construction method of chiral luminescent liquid crystal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004136878510000011
    Figure HDA0004136878510000011
  • Figure HDA0004136878510000012
    Figure HDA0004136878510000012
  • Figure HDA0004136878510000021
    Figure HDA0004136878510000021
Patent Text Reader

Abstract

The present invention relates to a circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters and a preparation method thereof. The present invention uses a surfactant as a liquid crystal template and performs supramolecular self-assembly with chiral copper nanoclusters modified with glutathione to prepare a circularly polarized luminescent chiral liquid crystal. The obtained circularly polarized luminescent chiral liquid crystal not only retains the liquid crystal properties under high concentrations of the surfactant, but also realizes the chirality modulation and amplification of the copper nanoclusters through the action of the liquid crystal template, and the chirality regulation of the circularly polarized luminescent chiral liquid crystal can be realized only by controlling the addition amount of the surfactant and the chiral copper nanoclusters. The preparation method is simple, the raw materials are cheap and easy to obtain, and the prepared chiral supramolecular liquid crystal has potential application prospects in the fields of chiral sensing, chiral recognition and chiral optical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters and a preparation method thereof, and belongs to the field of advanced optical materials. Background Art

[0002] Chirality, as a basic property of nature, is of vital importance in many fields (such as chemistry, biology, physics and materials science). The transmission of chiral information plays an important role in complex biological activities (including chiral recognition and chiral catalysis). Chiral functional materials with circularly polarized luminescence (CPL) properties have broad application prospects in optical data storage, CPL sensing, display, CPL switching, etc., and research in these areas has attracted great attention from scientists.

[0003] In recent years, chiral metal nanoclusters, as a special type of chiral coordination compounds, have attracted more and more attention due to their great potential application value in optics, electricity, magnetism, chiral catalysis and other important aspects. Research on their self-assembly ability and quantum size effect has received much attention. However, it is uncontrollable whether chiral metal nanoclusters can produce CPL in the excited state. In order to obtain chiral metal nanoclusters with CPL properties, it is usually necessary to have a complex synthesis process and select organic ligands with strong surface binding to the metal core, which has the disadvantages of long synthesis cycle and complex process. In previous studies, we found that the transfer and amplification of chirality through self-assembly can promote the expression of asymmetry at the aggregation level, which is expected to help construct chiral nanoclusters with high asymmetry factors (g lum ) of CPL material.

[0004] By using non-covalent interactions (such as π-π interactions, hydrogen bonds, and electrostatics) to drive the stacking mode and self-assembly behavior within the assembly, supramolecular systems can be used to easily and effectively transfer the chirality of chiral components to non-chiral molecules. Surfactant liquid crystals can achieve orderly arrangement of doped molecules by constructing a confined space. In the past, supramolecular liquid crystals constructed by metal nanoclusters and surfactants driven by non-covalent interactions were mainly used to study the fluorescence, crystal structure and phase behavior of supramolecular liquid crystals. For example, hydrophobic cations were introduced into hydrophilic gold nanoclusters, and amphiphilic assemblies were constructed by ion pairing reactions between anionic surface functional groups and cations, and the self-assembly behaviors in different solvents were studied (Yao QF, Yuan X, Yu Y, Yu Y, Xie JP, Lee J Y. Introducing Amphiphilicity to Noble Metal Nanoclusters via Phase-Transfer Driven Ion-Pairing Reaction. J. Am. Chem. Soc. 2015, 137(5), 2128–2136). However, there is almost no research on the chirality of chiral metal nanocluster-based supramolecular liquid crystals. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters and a preparation method thereof.

[0006] The present invention uses copper, which is easily available from commercial channels, inexpensive, and has high earth abundance, as a raw material to synthesize chiral copper nanoclusters as building blocks, and interacts with Triton X-100 through hydrogen bonds to construct a supramolecular assembly with ordered molecular arrangement in a colloidal self-assembly manner to obtain circularly polarized luminescent chiral liquid crystals, which are easy to produce CPL in an excited state. The method is simple to prepare, environmentally friendly, and highly economical. It broadens the construction method of chiral luminescent liquid crystals and provides a new idea for preparing doped liquid crystal materials with CPL activity.

[0007] Terminology Note:

[0008] GSH-Cu NCs: a chiral copper nanocluster with glutathione as its ligand, which exhibits strong luminescence properties in aqueous solution.

[0009] Triton X-100: It is a nonionic surfactant. It is easily soluble in water because of the strong hydrophilic functional groups in the molecule that form hydrogen bonds with water. It has the advantages of being non-toxic, low-priced, and highly stable.

[0010] In order to achieve the above object, the present invention adopts the following technical scheme:

[0011] A circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is obtained by using GSH-Cu NCs as chiral donors and Triton X-100 as liquid crystal template. The GSH-Cu NCs aqueous solution and Triton X-100 are co-assembled and regulated through hydrogen bond interaction.

[0012] According to the present invention, preferably, the chiral signal includes a CD signal and a CPL signal.

[0013] According to the present invention, preferably, the polarization texture of the circularly polarized luminescent chiral liquid crystal is a sector-shaped texture.

[0014] According to the present invention, preferably, the fluorescence excitation wavelength of the circularly polarized luminescent chiral liquid crystal is 300-385 nm, and the emission wavelength is 355-650 nm.

[0015] Most preferably, the fluorescence excitation wavelength of the circularly polarized luminescent chiral liquid crystal is 335 nm, and the emission wavelength is 425 nm.

[0016] The present invention also provides a method for preparing the circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters.

[0017] A method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters comprises the following steps:

[0018] The GSH-Cu NCs aqueous solution is mixed with a liquid crystal template surfactant, vortexed to obtain a mixed solution, and the mixed solution is allowed to stand in a constant temperature box for 20-30 hours to obtain a circularly polarized luminescent chiral liquid crystal.

[0019] Preferably according to the present invention, the surfactant is the surfactant Triton X-100.

[0020] According to the preferred embodiment of the present invention, the concentration of the GSH-Cu NCs aqueous solution is 0.56-30 mg·mL -1 .

[0021] Preferably according to the present invention, the mass concentration of the surfactant in the mixed solution is 2 to 55 wt %.

[0022] Preferably according to the present invention, the temperature of the thermostat is 18-25°C.

[0023] Preferably, according to the present invention, the GSH-Cu NCs aqueous solution is prepared by the following method:

[0024] Polyvinyl pyrrolidone (PVP) is dispersed in water and subjected to ultrasonic treatment. After the ultrasonic treatment, an alkali solution is added to the aqueous solution to adjust the pH to 4.0-6.0 to obtain a PVP solution. An L-ascorbic acid (L-AA) aqueous solution and copper sulfate (CuSO4 ) aqueous solution is mixed with PVP solution, reacted at room temperature for 4-8 days, dialyzed using a dialysis bag with a molecular weight cutoff of 12000-14000Da, the dialyzed copper cluster (Cu NCs) aqueous solution is mixed with glutathione (GSH) aqueous solution, the pH of the mixture is adjusted to 3.8-4.5, and allowed to stand for 1-4 days to obtain a GSH-Cu NCs aqueous solution.

[0025] According to the present invention, preferably, the concentration of the PVP solution is 5 to 100 mg·mL -1 , the concentration of L-ascorbic acid aqueous solution is 10-25 mg·mL -1 , CuSO 4 The concentration of aqueous solution is 5-20 mg·mL -1 .

[0026] Most preferably, the concentration of the PVP solution is 50 mg mL -1 , the concentration of L-ascorbic acid aqueous solution is 17.6 mg·mL -1 , CuSO 4 The concentration of aqueous solution is 15.9 mg·mL -1 .

[0027] According to the present invention, preferably, the PVP solution, the L-ascorbic acid aqueous solution and the copper sulfate (CuSO 4 ) aqueous solution in a mixing volume ratio of 100:10:1.

[0028] According to the present invention, preferably, the alkaline solution has a concentration of 1 mol·L -1 NaOH aqueous solution or 1 mol·L -1 of KOH aqueous solution.

[0029] According to the present invention, preferably, the ultrasonic frequency of the ultrasonic treatment is 30-50 kHz, the ultrasonic power is 80 W, and the ultrasonic time is 10 minutes.

[0030] According to the present invention, preferably, the concentration of glutathione aqueous solution is 20-80 mmol·L -1 .

[0031] Most preferably, the concentration of glutathione aqueous solution is 50mmol·L -1 .

[0032] According to the present invention, preferably, the volume ratio of the copper cluster (Cu NCs) aqueous solution to the glutathione (GSH) aqueous solution is 9:1.

[0033] According to the present invention, preferably, NaOH is added to adjust the pH of the mixture to 4.0.

[0034] The present invention can effectively regulate the change of supramolecular chirality signal of chiral supramolecular liquid crystal by changing the ratio of Triton X-100 liquid crystal template and chiral donor GSH-Cu NCs; circularly polarized luminescent chiral liquid crystal realizes the chirality transfer process and amplification of circularly polarized luminescence signal through orderly arrangement of chiral donor GSH-CuNCs in the liquid crystal template.

[0035] The regulation mechanism of the present invention is as follows: the hydrogen bonding effect between the liquid crystal template Triton X-100 and the chiral donor GSH-Cu NCs destroys the hydrogen bonding network inside the original surfactant, so that the surfactant and the chiral donor are co-assembled into a circularly polarized luminescent chiral liquid crystal, and the chiral behavior of the generated circularly polarized luminescent chiral liquid crystal depends on the ratio between the GSH-Cu NCs chiral donor and the liquid crystal template Triton X-100. By changing the ratio of the Triton X-100 liquid crystal template and the chiral donor GSH-Cu NCs, the hydrogen bonding effect between the two components is adjusted, and the chirality reversal of the chiral supramolecular liquid crystal is achieved. At the same time, the chirality transfer of the chiral supramolecular liquid crystal and the orderly regulation of the liquid crystal template improve the asymmetric expression of the supramolecular assembly, achieve CPL amplification, and increase the luminescence asymmetry factor.

[0036] Applications of circularly polarized luminescent chiral liquid crystals for novel luminescent probes, stimuli-responsive materials, asymmetric catalysis or chiral separation.

[0037] The outstanding features and beneficial effects of the present invention are:

[0038] 1. The present invention avoids a complicated synthesis process and obtains ordered metal nanocluster supramolecular aggregates by colloidal self-assembly. GSH-Cu NCs is used as a chiral donor and co-assembled with Triton X-100 through hydrogen bond interaction to regulate the chiral signal of the chiral copper nanocluster / Triton X-100 self-assembly, which has the advantages of low cost and convenient and controllable operation process.

[0039] 2. The present invention uses non-chiral lyotropic liquid crystal as a physical template. The hydrophobic region and the hydrophilic region of the surfactant in the lyotropic liquid crystal are spaced from each other and arranged in a periodic and orderly manner. Using this unique anisotropic structure as a template to regulate the arrangement of chiral components may give the assembly more superior performance and is more conducive to exploring the source of chirality, avoiding the cholesteric phase or smectic phase liquid crystal that has been more widely studied in previous chirality studies.

[0040] 3. The present invention realizes the chirality transfer from the chiral donor to the supramolecular assembly, and only needs to change the ratio between the GSH-CuNCs chiral donor and the liquid crystal template Triton X-100, without changing the inherent molecular chirality of the chiral donor, to achieve the circularly polarized luminescent chiral liquid crystal with adjustable optical activity, thus overcoming the defects of the prior art. The orderly arrangement of chiral metal nanoclusters in the liquid crystal realizes the spatial amplification of chirality and the improvement of the luminescence asymmetry factor.

[0041] 4. The GSH-Cu NCs used in the present invention is a metal cluster compound, which belongs to a new type of organic-inorganic hybrid material and has the characteristics of excellent optical properties and rich composition. Different from the widely studied gold and silver precious metal clusters, copper nanoclusters have the advantages of high earth abundance, low price and easy access, which is conducive to broadening the application of copper nanoclusters.

[0042] 5. The chiral copper nanoclusters and preparation methods provided by the present invention require low-cost raw materials and are simple to operate. They have broad application prospects in the fields of new luminescent probes, stimuli-responsive materials, asymmetric catalysis, chiral separation, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is the Fourier transform infrared spectrum (FTIR) of GSH-Cu NCs obtained in Example 1.

[0044] Figure 2 : CD spectra and CPL spectra of GSH-Cu NCs obtained in Example 1; a is the CD spectrum, and b is the CPL spectrum.

[0045] Figure 3 The polarization texture and fluorescence emission spectrum of the circularly polarized luminescent chiral liquid crystal obtained in Example 1; a is the polarization image, and b is the fluorescence emission spectrum.

[0046] Figure 4 The CD spectrum and CPL spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 1; a is the CD spectrum, and b is the CPL spectrum.

[0047] Figure 5 a is the FTIR graph of the circularly polarized luminescent chiral liquid crystal prepared in Example 1-3, Figure 5 b is the small angle X-ray scattering (SAXS) pattern of the circularly polarized luminescent chiral liquid crystal prepared in Example 1.

[0048] Figure 6 The H NMR spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 1 ( 1 1H NMR).

[0049] Figure 7a is the ultraviolet visible absorption spectrum (UV-vis) of GSH-Cu NCs prepared in Example 2, Figure 7 b is the electrospray ionization mass spectrum (ESI-MS) of GSH-Cu NCs prepared in Example 3.

[0050] Figure 8 Polarization texture of the circularly polarized luminescent chiral liquid crystal prepared in Example 4.

[0051] Fig. 9 CD spectrum and CPL spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 4; a is the CD spectrum, and b is the CPL spectrum.

[0052] Fig.10 Polarization texture of the circularly polarized luminescent chiral liquid crystal prepared in Example 5.

[0053] Fig.11 CD spectrum and CPL spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 5; a is the CD spectrum, and b is the CPL spectrum.

[0054] Fig.12 Polarization texture of the circularly polarized luminescent chiral liquid crystal prepared in Example 6.

[0055] Fig.13 CD spectrum and CPL spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 6; a is the CD spectrum, and b is the CPL spectrum.

[0056] Fig.14 Polarization texture of the circularly polarized luminescent chiral liquid crystal prepared in Example 7.

[0057] Fig.15 The CD spectrum and CPL spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Example 7 a is the CD spectrum, and b is the CPL spectrum.

[0058] Fig.16 CD spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Comparative Example 1.

[0059] Fig.17 CD spectrum of the circularly polarized luminescent chiral liquid crystal prepared in Comparative Example 2. Specific implementation methods

[0060] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0061] The raw materials used in the examples are conventional raw materials, commercially available products, including: PVP and CuSO 4, available from Tianjin Komiou Chemical Reagent Co., Ltd., L-AA and L-GSH, available from Sinopharm Chemical Reagent Co., Ltd., and Triton X-100, available from Sigma-Aldrich, were used directly without further purification before use.

[0062] The KQ5200DE instrument is a prior art.

[0063] Example 1

[0064] The preparation method of circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters comprises the following steps:

[0065] (1) Synthesis of GSH-Cu NCs

[0066] PVP (500 mg) was dispersed in 10 mL of water and subjected to ultrasonic treatment for 10 min (80 W, 40 kHz) on a KQ5200DE instrument. After ultrasonic treatment, NaOH (1 mol·L -1 ), the pH was adjusted to 6.0 to obtain a PVP solution, L-AA (17.6 mg) was dispersed in 1 mL of water to obtain an L-AA aqueous solution, CuSO 4 (1.6 mg) was dispersed in 0.1 mL of water to obtain CuSO 4 aqueous solution, L-AA aqueous solution, CuSO 4 The aqueous solution was mixed with the PVP solution and reacted at room temperature for 6 days. The mixture was dialyzed using a dialysis bag with a molecular weight cutoff of 12000-14000Da. Glutathione was dispersed in water to obtain a concentration of 50mmol·L -1 glutathione aqueous solution, adding NaOH to adjust the pH to 4.0, mixing the dialyzed Cu NCs aqueous solution with the GSH solution at a volume ratio of 9:1, adjusting the pH of the mixture to 4.0, and leaving it for 2 days to obtain a GSH-Cu NCs aqueous solution;

[0067] The FTIR spectrum of GSH-Cu NCs was obtained as Figure 1 As shown. Figure 1 It can be seen that the ligand glutathione and the copper core are connected through Cu-S.

[0068] The CD spectra of GSH-Cu NCs are shown in Figure 2 As shown in a. Figure 2 It can be seen that GSH-Cu NCs have a positive cotton effect in the wavelength range of 180-200nm.

[0069] The CPL spectrum of GSH-Cu NCs is obtained as Figure 2 As shown in b. Figure 2It can be seen that GSH-Cu NCs exhibit a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.011.

[0070] (2) Preparation of supramolecular chiral liquid crystals

[0071] Accurately weigh 1.93 g of Triton X-100 and dissolve it in 2 mL of GSH-Cu NCs (28 mg mL -1 ) aqueous solution, vortex for 30 seconds to mix evenly to obtain a mixed solution, in which the mass concentration of Triton X-100 is 50wt%, and the mixed solution is allowed to stand in a constant temperature box at 20°C for 24 hours to obtain circularly polarized luminescent chiral liquid crystal.

[0072] The polarization texture of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 3 As shown in a. Figure 3 It can be seen that the polarization texture of the supramolecular chiral liquid crystal is a fan-shaped texture.

[0073] The fluorescence emission spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 3 As shown in b. Figure 3 It can be seen that the supramolecular chiral liquid crystal emits 425nm blue fluorescence under 335nm excitation.

[0074] The CD spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 4 As shown in a. Figure 4 a It can be seen that the circularly polarized luminescent chiral liquid crystal exhibits a negative cotton effect in the range of 250-300nm, realizing the chirality transfer from the chiral component to the circularly polarized luminescent chiral liquid crystal.

[0075] The CPL spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 4 As shown in b. Figure 4 b It can be seen that the circularly polarized luminescent chiral liquid crystal exhibits a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.021. Circular polarization amplification is achieved due to the chiral transfer and the orderly arrangement of the liquid crystal template.

[0076] The FTIR spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 5 As shown in a. Figure 5 a It can be seen that the formation of circularly polarized luminescent chiral liquid crystal is driven by hydrogen bonds.

[0077] This embodiment obtains circularly polarized luminescent chiral liquid crystal 1 H NMR Figure 6 As shown. Figure 6 It can be seen that the formation of circularly polarized luminescent chiral liquid crystals driven by hydrogen bonds leads to a stronger nuclear magnetic peak and a narrower half-peak width.

[0078] The SAXS spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 5 As shown in b. Figure 5 b It can be seen that the formation of circularly polarized luminescent chiral liquid crystals does not change the hexagonal phase configuration of Triton X-100, but makes its stacking more compact.

[0079] Example 2

[0080] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0081] In step (1), after ultrasonic treatment, KOH aqueous solution (1 mol·L -1 ), and the pH was adjusted to 6.0. Other steps and conditions were consistent with those in Example 1.

[0082] The UV-vis spectra of GSH-Cu NCs were obtained as Figure 7 As shown in a. Figure 7 a It can be seen that there is ultraviolet absorption near 385nm, which proves the formation of copper nanoclusters.

[0083] The FTIR spectrum of circularly polarized luminescent chiral liquid crystal is as follows: Figure 5 As shown in a. Figure 5 a It can be seen that hydrogen bonding drives the formation of circularly polarized luminescent chiral liquid crystals.

[0084] Example 3

[0085] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0086] In step (1), the pH of the glutathione aqueous solution was adjusted from 4.0 to 3.8, and the other steps and conditions were the same as those in Example 1.

[0087] The electrospray ionization mass spectra of GSH-Cu NCs were obtained as Figure 7 As shown in b. Figure 7 b It can be seen that the main component of GSH-Cu NCs is Cu 5 GSH 2 .

[0088] The FTIR spectrum of circularly polarized luminescent chiral liquid crystal is as follows: Figure 5 As shown in a. Figure 5 a It can be seen that hydrogen bonding drives the formation of circularly polarized luminescent chiral liquid crystals.

[0089] Example 4

[0090] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0091] Step (2): accurately weigh 1.29 g of Triton X-100 and dissolve it in 2 mL of GSH-Cu NCs (28 mg mL -1 ) aqueous solution, vortexed for 30 seconds to mix evenly to obtain a mixed solution, in which the mass concentration of Triton X-100 is 40wt%, and then allowed to stand in a constant temperature box at 20°C for 24 hours to obtain circularly polarized luminescent chiral liquid crystal.

[0092] The polarization texture of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Figure 8 As shown. Figure 8 It can be seen that the polarization texture of the supramolecular chiral liquid crystal is a fan-shaped texture.

[0093] The CD spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig. 9 As shown in a. Fig. 9 a It can be seen that the supramolecular chiral liquid crystal exhibits a negative cotton effect in the range of 250-300nm.

[0094] The CPL spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig. 9 As shown in b. Fig. 9 b It can be seen that the circularly polarized luminescent chiral liquid crystal exhibits a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.018.

[0095] Example 5

[0096] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0097] Step (2): GSH-Cu NCs aqueous solution (28 mg mL -1 ) was diluted to 2.24 mg mL -1 Concentration solution, accurately weigh 1.93g of Triton X-100 and dissolve it in 2mL of the diluted GSH-Cu NCs aqueous solution, vortex for 30s to mix it evenly, to obtain a mixed solution, the mass concentration of Triton X-100 in the mixed solution is 50wt%, and stand in a constant temperature box at 20℃ for 24 hours to obtain circularly polarized luminescent chiral liquid crystal.

[0098] The polarization texture of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.10 As shown. Fig.10 It can be seen that the polarization texture of the supramolecular chiral liquid crystal is a fan-shaped texture.

[0099] The CD spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.11 As shown in a. Fig.11 a It can be seen that circularly polarized luminescent chiral liquid crystal exhibits a negative cotton effect in the range of 250-300nm.

[0100] The CPL spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.11 As shown in b. Fig.11 b It can be seen that the circularly polarized luminescent chiral liquid crystal exhibits a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.023.

[0101] Example 6

[0102] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0103] Step (2): GSH-Cu NCs aqueous solution (28 mg mL -1 ) was diluted tenfold to a concentration of 2.8 mg mL -1 , accurately weigh 1.93 g of Triton X-100 and dissolve it in 2 mL of the diluted GSH-Cu NCs aqueous solution, vortex for 30 seconds to mix it evenly, to obtain a mixed solution, the mass concentration of Triton X-100 in the mixed solution is 50 wt%, and then stand in a constant temperature box at 20°C for 24 hours to obtain circularly polarized luminescent chiral liquid crystals.

[0104] The polarization texture of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.12 As shown. Fig.12 It can be seen that the polarization texture of the supramolecular chiral liquid crystal is a fan-shaped texture.

[0105] The CD spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.13 As shown in a. Fig.13 a It can be seen that the supramolecular chiral liquid crystal exhibits a positive cotton effect in the range of 250-300nm.

[0106] The CPL spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.13 As shown in b. Fig.13 b It can be seen that the supramolecular chiral liquid crystal exhibits a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.021.

[0107] Example 7

[0108] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0109] Step (2): GSH-Cu NCs aqueous solution (28 mg mL -1 ) was diluted twenty times to a concentration of 1.4 mg mL -1 , accurately weigh 1.93 g of Triton X-100 and dissolve it in 2 mL of the diluted GSH-Cu NCs aqueous solution, vortex for 30 seconds to mix it evenly, to obtain a mixed solution, the mass concentration of Triton X-100 in the mixed solution is 50 wt%, and then stand in a constant temperature box at 20°C for 24 hours to obtain supramolecular chiral liquid crystals.

[0110] The polarization texture of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.14 As shown. Fig.14 It can be seen that the polarization texture of the circularly polarized luminescent chiral liquid crystal is a fan-shaped texture.

[0111] The CD spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.15 As shown in a. Fig.15 a It can be seen that the supramolecular chiral liquid crystal exhibits a positive cotton effect in the range of 250-300nm.

[0112] The CPL spectrum of the circularly polarized luminescent chiral liquid crystal obtained in this embodiment is as follows: Fig.15 As shown in b. Fig.15 b It can be seen that the supramolecular chiral liquid crystal exhibits a strong positive CPL signal at 455nm, and the average absolute value of the luminescence asymmetry factor is 0.020.

[0113] In summary, it can be seen from Examples 1 and 4-7 that the chirality inversion of the chiral supramolecular liquid crystal can be achieved by simply changing the ratio of the Triton X-100 liquid crystal template to the chiral donor GSH-Cu NCs.

[0114] Comparative Example 1

[0115] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0116] Triton X-100 was replaced by Tyloxapol, and the mass concentrations of Tyloxapol in the mixed solution were 12.5 wt % and 25 wt %, respectively. Other conditions and parameters were the same as those in step (2) of Example 1.

[0117] The CD spectrum of the product is as follows Fig.16 As shown. Fig.16 It can be seen that replacing Triton X-100 with Tyloxapol cannot achieve the chirality transfer of GSH-Cu NCs from the chiral donor to the supramolecular assembly.

[0118] Comparative Example 2

[0119] The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is the same as that described in Example 1, except that:

[0120] Tetraethylene glycol monolauryl ether (C 12 E 4 ) replaced Triton X-100, the mass concentrations of tetraethylene glycol monolauryl ether in the mixed solution were 12.5wt% and 25wt%, respectively. Other conditions and parameters were the same as those in step (2) of Example 1.

[0121] The CD spectrum of the product is as follows Fig.17 As shown. Fig.17 It can be seen that using C 12 E 4 Replacing Triton X-100 could not achieve the chirality transfer of GSH-Cu NCs from the chiral donor to the supramolecular assembly.

[0122] In summary, it can be seen that the liquid crystal template Triton X-100 is crucial, and random replacement of the liquid crystal template cannot achieve the chirality transfer from the chiral donor to the supramolecular assembly.

[0123] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters, which is obtained by using GSH-Cu NCs as chiral donors and Triton X-100 as liquid crystal templates. GSH-Cu NCs aqueous solution and Triton X-100 are co-assembled and regulated through hydrogen bond interaction. GSH-Cu NCs is a chiral copper nanocluster with glutathione as the ligand, which exhibits strong luminescence properties in aqueous solution. The circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters is prepared by the following method: a GSH-CuNCs aqueous solution is mixed with a liquid crystal template surfactant, vortexed to obtain a mixed solution, and allowed to stand in a constant temperature box for 20-30 hours to obtain a circularly polarized luminescent chiral liquid crystal, wherein the concentration of the GSH-CuNCs aqueous solution is 0.56-30 mg·mL -1 , the mass concentration of surfactant in the mixed solution is 40-55%.

2. The circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters according to claim 1, characterized in that: The chiral signal includes a CD signal and a CPL signal. The polarization texture of the circularly polarized luminescent chiral liquid crystal is a fan-shaped texture. The fluorescence excitation wavelength of the circularly polarized luminescent chiral liquid crystal is 300-385 nm, and the emission wavelength is 355-650 nm.

3. The method for preparing circularly polarized luminescent chiral liquid crystal based on chiral copper nanoclusters according to claim 1, comprising the following steps: The GSH-Cu NCs aqueous solution was mixed with the liquid crystal template surfactant, vortexed, and the mixed solution was placed in a constant temperature box for 20-30 hours to obtain circularly polarized luminescent chiral liquid crystals. The concentration of the GSH-Cu NCs aqueous solution was 0.56-30 mg·mL -1 , the mass concentration of surfactant in the mixed solution is 40-55%.

4. The method according to claim 3, characterized in that: The temperature of the constant temperature box is 18 ~ 25 ℃.

5. The method according to claim 3, characterized in that: The GSH-Cu NCs aqueous solution was prepared as follows: Polyvinyl pyrrolidone (PVP) is dispersed in water and subjected to ultrasonic treatment. After the ultrasonic treatment, a sodium hydroxide (NaOH) solution is added to the aqueous solution to adjust the pH to 4.0-6.0 to obtain a PVP solution. An L-ascorbic acid (L-AA) aqueous solution and a copper sulfate (CuSO4) aqueous solution are mixed with the PVP solution and reacted at room temperature for 4-8 days. The solution is dialyzed using a dialysis bag with a molecular weight cutoff of 12000-14000 Da. The dialyzed copper cluster (Cu NCs) aqueous solution is mixed with a glutathione (GSH) aqueous solution, the pH of the mixture is adjusted to 3.8-4.5, and the mixture is allowed to stand for 1-4 days to obtain a GSH-Cu NCs aqueous solution.

6. The method according to claim 5, characterized in that The concentration of PVP solution is 5~100mg·mL -1 , the concentration of L-ascorbic acid aqueous solution is 10-25 mg·mL -1 , the concentration of CuSO4 aqueous solution is 5-20mg·mL -1 ; The volume ratio of the PVP solution, L-ascorbic acid aqueous solution and copper sulfate (CuSO4) aqueous solution was 100:10:1, and the concentration of the NaOH aqueous solution was 1 mol·L -1 ; The ultrasonic frequency of the ultrasonic treatment was 30-50 kHz, the ultrasonic power was 80 W, and the ultrasonic time was 10 minutes; The concentration of glutathione aqueous solution is 20-80mmol·L -1 ; The copper cluster (Cu NCs) aqueous solution and the glutathione (GSH) aqueous solution were mixed in a volume ratio of 9:1, and NaOH was added to adjust the pH of the mixture to 4.

0.

7. Use of the circularly polarized luminescent chiral liquid crystal according to claim 1 for preparing new luminescent probes, stimuli-responsive materials, or for asymmetric catalysis or chiral separation.

Citation Information

Patent Citations

  • Copper-based circularly-polarized luminescent material and preparation and application thereof

    CN110105378A

  • Copper (I) alkyne cluster capable of realizing aggregation-induced luminescence and circularly-polarized luminescence

    CN110467631A